2016
DOI: 10.1089/jmf.2016.0052
|View full text |Cite
|
Sign up to set email alerts
|

Pereskia aculeata Miller Flour: Metabolic Effects and Composition

Abstract: Pereskia aculeata Miller is known in Brazil as ora-pro-nobis (OPN) and has been used commonly in the folklore medicine. The purpose of our study was to evaluate the composition and the effects of OPN flour on the metabolic profile and intestinal motility of Wistar rats. Animals were divided randomly into five groups (n = 10): G1 (control group) and G2 (treated with OPN flour). For the intestinal motility: G3 (control group), G4 (treated with senne), and G5 (treated with OPN flour). After 40 days, G1 and G2 wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
2
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 28 publications
1
19
2
5
Order By: Relevance
“…The total phenolic compounds content in orapro-nobis fruits were higher than those observed in some traditional fruits, such as pineapple (33 mg GAE 100 g -1 ), papaya (33.4 mg GAE 100 g -1 ), and mango (41.1 mg GAE 100 g -1 ) (SEPTEMBRE-MALATERRE et al, 2016). The contents of bioactive compounds in ora-pro-nobis fruits explicit their potential to complement the human diet (BARBALHO et al, 2016). The antioxidant capacity of native cacti fruits in Brazil is of most importance, since the food-health relationship is being explored and highlighted by the scientific community in this scenario (AGOSTINI-COSTA et al, 2012;ARAUJO et al, 2016;BARBALHO et al, 2016;MORZELLE et al, 2015).…”
Section: Frutos De Ora-pro-nóbis (Pereskia Aculeata Miller) Maduros Ementioning
confidence: 83%
See 2 more Smart Citations
“…The total phenolic compounds content in orapro-nobis fruits were higher than those observed in some traditional fruits, such as pineapple (33 mg GAE 100 g -1 ), papaya (33.4 mg GAE 100 g -1 ), and mango (41.1 mg GAE 100 g -1 ) (SEPTEMBRE-MALATERRE et al, 2016). The contents of bioactive compounds in ora-pro-nobis fruits explicit their potential to complement the human diet (BARBALHO et al, 2016). The antioxidant capacity of native cacti fruits in Brazil is of most importance, since the food-health relationship is being explored and highlighted by the scientific community in this scenario (AGOSTINI-COSTA et al, 2012;ARAUJO et al, 2016;BARBALHO et al, 2016;MORZELLE et al, 2015).…”
Section: Frutos De Ora-pro-nóbis (Pereskia Aculeata Miller) Maduros Ementioning
confidence: 83%
“…Although the fruits of ora-pro-nobis have been underused, they are commonly recognized as nutraceutic, or functional and medicinal food, with anti-inflammatory and antinociceptive effects (BARBALHO et al 2016;SILVA JÚNIOR et al, 2010). The ora-pro-nobis fruits have oval, piriform or rounded shape, yellowish-green, yellow-orange or reddish color (BRASIL, 2010).…”
Section: Frutos De Ora-pro-nóbis (Pereskia Aculeata Miller) Maduros Ementioning
confidence: 99%
See 1 more Smart Citation
“…Only two studies were found that evaluated these effects of ora‐pro‐nobis flour in rats. One study found a reduction of visceral fat and lipid levels, as well as increased levels of HDL‐c (Barbalho et al, ). The other study found a reduction in body weight and hepatic lipid levels, using the flour of the leaves of P. grandifolia , which belongs to the same family as P. aculeata (Elisa et al, ) .…”
Section: Discussionmentioning
confidence: 99%
“…However, these prebiotic effects, as well as other possible beneficial effects, should be confirmed in clinical trials. Studies in animals have already shown that ora-pro-nobis improved intestinal motility and affected the acute and chronic antiinflammatory activity of rats (Barbalho et al, 2016;Pinto, Machado, et al, 2015). Thus, the objective of this study was to investigate the influence of ora-pro-nobis flour on the adhesion of probiotics to intestinal epithelial cells and to evaluate the effect of a product based on this flour on gastrointestinal symptoms, weight, body fat, glycemia, and lipid profile in overweight men.…”
mentioning
confidence: 99%